The Statesman's Yearbook 2018 The Politics, Cultures and Economies of the World (The Statesman's Yearbook,, 2018)
THE STATESMAN'S YEARBOOK 2018 This classic reference work presents a political, economic and social account of every country of the world together with facts and analysis. The 2018 edition includes: Revised and updated biographical profiles of all current leaders Extensive updates to country economic overviews Expanded and updated historical introductions Chronology of key political events from April 2016 to March 2017 Comprehensive coverage of major international organizations 2016 in 1,000 words - a summary of the key events that dominated the world during the year SPECIAL FEATURE: The Rise and Rise of Populism by Barry Turner NEW: Statistics on access to clean water worldwide NEW: Population projections for every country in 2020 DID YOU KNOW? China overtook Germany as the country with the highest solar energy generating capacity in 2015 Estonia was the first country to use internet voting at a national election, for its 2007 parliamentary election In the 2016 presidential election in Palau, Tommy Remengesau Jr defeated his brother-in-law Surangel Whipps Jr In Papua New Guinea, 60% of the population does not have access to safe water The capital of New York State is not New York City, but Albany.